Innovation of Female Urinary Catheterization Training Mannequin with Sensor System (Samila) - Chotiban, Pattamamas; Nawsuwan, Kittiporn; Singweratham, Noppcha (Princess of Naradhiwas University Journal, 2021)
The purpose of this research and development were 1) to create and develop a female urinary catheterization training mannequin with sensor system (Samila) and 2) to evaluate the effectiveness of the training mannequin. The study was divided into two phases as follows: 1) the design and development of the female urinary catheterization training mannequin with sensor system consisting of need assessment, concepts and literature review, the training mannequin creation, tryout, and improvement; and 2) the evaluation of the effectiveness of the training mannequin. Population was 72 nursing students studying in the third year, academic year of 2019. The instrument used in this research was the censored female urinary catheterization training mannequin which its IOC was ranged from .67 to 1.00, and the Cronbach’s alpha coefficient was equal to .91. Data were analyzed by paired t-test. The results of this study revealed as follows: The female urinary catheterization training mannequin with sensor system (Samila) was made from natural latex and synthetic latex resin. Its appearance is a wooden box with anatomical pads attached to the female genitalia. The box was made from plastwood, which is lightweight, durable and non-wet. The interior of the mannequin contains a uterus and a vagina installed inside the mannequin by connecting to the clitoris plate. There is a simulated bladder that can actually be filled with artificial urine, and flow through the catheter. There is a loud sound when the catheter is inserted in the vagina. The effectiveness of female urinary catheterization training mannequin with sensor system (Samila) had a statistical significantly higher mean score than the original mannequin at the .001 level (p<.001). After using the training mannequin, 100% of the nursing students could practice inserting a female urinary catheter correctly. Therefore, Boromarajonani College of nursing, Songkhla should encourage students to use the developed training mannequin (Samila) for those who practice on ward for the first time or those who need to practice in nursing laboratory, as well as students who want to bring the mannequin back to their dormitory for practicing in order to build their confidence and to perform correctly in inserting a female urinary catheter before going on ward.